Prophylactic Nailing of Incomplete Atypical Femoral Fractures - Chang-Wug Oh; Jong-Keon Oh; Ki-Chul Park; Joon-Woo Kim; Yong-Cheol Yoon (The Scientific World Journal)
Introduction. Recent reports have described the occurrence of low-energy subtrochanteric and femoral shaft fractures associated with long-term bisphosphonate use. Although information regarding the surgical treatment of these atypical femoral fractures is increasing, it is unclear if the preventive operation is useful in incomplete fractures. This study examined the results of preventive intramedullary nailing for incomplete atypical femoral fractures. Material and Methods. A retrospective search was conducted for patients older than 50 years receiving bisphosphonate therapy, with incomplete, nondisplaced fractures in either the subtrochanteric or diaphyseal area of the femur. Seventeen patients with a total of 20 incomplete, non-displaced lesions were included. The mean duration of bisphosphonate use was 50.5 months. Eleven of the 17 (64.7%) patients had complete or incomplete fractures on the contralateral femur. All were treated with prophylactic fixation of an intramedullary (IM) nail. The minimum followup was 12 months. Results. All cases healed with a mean period of 14.3 weeks. Nineteen of the 20 cases healed with the dissolution of incomplete fractures of the lateral aspect. A complete fracture developed at the time of nailing in one patient, but it healed with callus bridging. Conclusion. IM nailing appears to be a reliable way of preventing the progress of incomplete atypical femoral fractures.